Some Aspects of Drug Induced Nephrotoxicity Assessment - E. A. Sokova; V. V. Arkhipov; I. A. Mazerkina; O. V. Muslimova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2020)
About 14‒23% of all clinically used drugs have nephrotoxic potential and are a frequent cause of acute and chronic kidney problems. Acute kidney injury (AKI) is associated with a high risk of repeat hospitalisation, complications, and mortality in adults and children. The aim of the study was to provide an overview of the current approaches to the assessment of drug induced nephrotoxicity. The paper summarises pathogenetic mechanisms of drug induced kidney injury as well as molecular mechanisms at the drug transporters level. It analyses risk factors for drug induced kidney injury-age, sex, ethnicity, comorbidities (chronic kidney disease, diabetes, cardiovascular disease, immune disorders, sepsis, etc.), drug dosage and duration of therapy, pharmacokinetics of drugs, combinations of potentially nephrotoxic drugs, genetic determinants of drug metabolism and transport, etc. It was demonstrated that the traditional nephrotoxicity markers-serum creatinine and urine output-have low sensitivity as indicators of early renal damage. Therefore, new kidney biomarkers are being sought for in order to be used in AKI diagnosis and monitoring in patients with different comorbidities. Some of these biomarkers are already used in drug development, preclinical and clinical trials for assessment and prediction of drug safety. The analysis showed that none of these new kidney biomarkers could be used as an all-purpose tool in routine clinical practice. The development of new AKI biomarkers is a long-range objective and is the path toward early diagnosis and successful treatment of drug-induced nephrotoxicity.